Timed artificial insemination conception rates in response to a progesterone insert in lactating dairy cows - C.A Martel; B.S. Buttery; M.G. Burns; W.E. Brown (Kansas Agricultural Experiment Station Research Reports, 2007)
Our objective was to determine the effectiveness of exogenous progesterone in the form of an intravaginal insert (controlled internal drug release, CIDR) in conjunction with an ovulation synchronization protocol in lactating dairy cows. Cows received a Presynch protocol (two injections of prostaglandin F2α[PGF2α] 14 days apart) beginning 30 and 36 days in milk, respectively, in two herds. Cows were inseminated after the second Presynch injection when estrus was detected. Remaining cows were treated with the Ovsynch protocol, and alternate cows were assigned randomly to receive a progesterone insert(CIDR). Blood was collected, and body condition scores (BCS) were assigned to treated cows. Pregnancy status was confirmed by palpation on day 38 post timed AI (TAI) and verified again 4 weeks later. Progesterone increased conception rates in treated cows when compared with controls (38 vs. 24%), but did not differ from early inseminated cows(38%). Pregnancy loss was numerically less in progesterone-treated cows than in controls(4.4 vs. 11.8%).; Dairy Day, 2007, Kansas State University, Manhattan, KS, 2007; Dairy Research, 2007 is known as Dairy Day, 2007
Keywords: Dairy Day; 2007; Kansas Agricultural Experiment Station contribution; no. 08-127-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 984; Dairy; CIDR; Ovsynch; GnRH; PGF2α